The N6-Methyladenosine Modification and Its Role in mRNA Metabolism and Gastrointestinal Tract Disease - Cai, Teng; Atteh, Lawrence Lawer; Zhang, Xianzhuo; Huang, Chongfei; Bai, Mingzhen; Ma, Haidong; Zhang, Chao; Fu, Wenkang; Gao, Long; Lin, Yanyan; Meng, Wenbo (Frontiers in Surgery, 2022)
N6-Methyladenosine (m6A) is the most abundant internal modification of messenger RNA (mRNA) in higher eukaryotes. Under actions of methyltransferase, demethylase and methyl-binding protein, m6A resulting from RNA methylation becomes dynamic and reversible, similar to DNA methylation, allowing it to participate in various gene expression process, such as splicing, transport, translation, and degradation. The most common tumors are those of the digestive system, and research on these tumors has flourished since the discovery of m6A. Overall, further analysis of the mechanism of m6A and its role in tumors may contribute to new ideas for the treatment of tumors. Here, knowledge of m6A-related proteins, mRNA metabolism and their application in digestive system tumors are reviewed.